The over-35s: early intervention in psychosis services entering uncharted territory. (24th May 2018) - Clay, Felix; Allan, Sophie; Lai, Serena; Laverty, Siona; Jagger, Grace; Treise, Cate; Perez, Jesus
Abstract : Aims and method: Following the introduction of new standards for early intervention in psychosis (EIP) in England, EIP services are accepting referrals for people aged 35–65. The Cambridgeshire and Peterborough EIP service (CAMEO) aimed to explore the immediate implications for the service, especially with regards to referral numbers and sources. Data were collected from April 2016 to June 2017. Results: Referrals for over-35s represented 25.7% of all new referrals. Fifty per cent of referrals for over-35s were accepted onto caseload (40.2% for under-35s). The over-35s were more likely to be referred from acute and secondary mental health services ( P < 0.01) and had longer durations of untreated psychosis than the under-35s ( P = 0.02). Clinical implications: CAMEO has received a significantly higher number of referrals as a result of age inclusivity, with an increased proportion of patients suffering from severe, acute psychotic presentations and existing mental health difficulties. This has implications for service planning. Declaration of interest: None.